A alienação social e o seu impacto no bem-estar dos adolescentes portugueses - Tomé, Gina (2019)
The aim of this study was to analyse the social alienation impact on the feelings of belonging to a group, friends’ relationships and wellbeing of Portuguese adolescents. Methods: A total of 5695 Portuguese adolescents with a mean age of 15.46 (SD=1.80), attending the 8th, 10th and 12th years of schooling in mainland Portugal were included in the Health Behaviour in School-aged Children (HBSC) study. Two models of path analysis were executed, one for the more resilient group of adolescents and one for the less resilient group, where it was found that the negative impact of social alienation on adolescents’ wellbeing was greater in the less resilient group. The friend’s relationship appears associated with less social alienation, as well as the feelings of belonging to a group, in both groups of resilience, nevertheless in the less resilient group the impact of the feelings of belonging reduces while the impact of the relation with the friends increases. The negative impact of social alienation on the wellbeing of adolescents is evident and it is essential to promote skills that prevent these consequences and promote the well-being of adolescents. Resilience emerges as a protective factor for the negative consequences of social alienation. Presented results strengthen the need to implement among adolescents’ programs that promote their personal and social skills with emphasis on resilience.